Catégorisation des plantes et des entités étiologiques chez les Yanesha (piémont amazonien du Pérou) - Céline Valadeau (Bulletin de l'Institut Français d'Études Andines, 2012)
Vernacular categorization systems have been studied for several years. In this article, the purpose is to analyze ethnobotanical and ethnographic data of the plants by the Yanesh of the high Peruvian Amazon in central Peru. The first focus of this study is to define the different known etiological agents. This enables us to identify the causes of a negative impact on health. In this context, healing plants are studied using myths and a linguistic study of plant names. The second focus of this article shows how the vernacular classification of etiologic entities and plants can be seen as constituting a single logical system. These systems of classification overlap and provide a key to understanding the articulation of the system by which the Yanesha classify illness sha and the logic underlying the naming of plants utilized in the event of illness.